2021
DOI: 10.1177/20587384211063976
|View full text |Cite
|
Sign up to set email alerts
|

Systemic corticosteroids for management of COVID-19: Saving lives or causing harm?

Abstract: The underlying cause of many complications associated with severe COVID-19 is attributed to the inflammatory cytokine storm that leads to acute respiratory distress syndrome (ARDS), which appears to be the leading cause of death in COVID-19. Systemic corticosteroids have anti-inflammatory activity through repression of pro-inflammatory genes and inhibition of inflammatory cytokines, which makes them a potential medical intervention to diminish the upregulated inflammatory response. Early in the severe acute re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 82 publications
0
16
0
Order By: Relevance
“…The timing of administering corticosteroids is one of the key points for improving the pathophysiology of COVID-19. In a previous RECOVERY Trial, the mortality benefit of corticosteroid therapy in COVID-19 was only evident in those with a symptom duration of seven days or more ( 6 , 20 ). However, a higher death rate in the dexamethasone group was observed in patients with a symptom duration of fewer than seven days ( 20 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The timing of administering corticosteroids is one of the key points for improving the pathophysiology of COVID-19. In a previous RECOVERY Trial, the mortality benefit of corticosteroid therapy in COVID-19 was only evident in those with a symptom duration of seven days or more ( 6 , 20 ). However, a higher death rate in the dexamethasone group was observed in patients with a symptom duration of fewer than seven days ( 20 ).…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that administering corticosteroids too early in the phase of COVID-19 lowers the inflammatory status and disease severity, increasing the viral load and causing harm to these patients ( 6 ). Thus, a scoring system that can predict hyper-inflammation rates requiring corticosteroid administration is required.…”
Section: Introductionmentioning
confidence: 99%
“…Dexamethasone is an example of a drug used for this purpose since it lowers the innate immune response of hosts. It has been successfully used in the UK to reduce the mortality of the severely-ill COVID-19 patients [95] , Dexamethasone suffers from serious side effects, since corticosteroids reduce viral clearance, increase secondary infections and perturb metabolism [96] , [97] . Similar to dexamethasone, melatonin downregulates the innate immunity but unlike the corticosteroid, melatonin promotes the adaptive immunity as well as inhibits the entrance and replication of the SARS-CcV-2.…”
Section: Discussionmentioning
confidence: 99%
“…After the initial uncertainty during the onset of COVID-19 pandemic, glucocorticosteroids, mainy dexamethasone, are a standard therapy in severe disease course [ 87 ]. However, due to their immunosuppressive potential and potential harms, high doses of corticosteroids should be avoided early in the disease course, when patients do not require oxygen support [ 88 ].…”
Section: Immune Response To Sars-cov-2 Infectionmentioning
confidence: 99%